The cyber domain in the Ukraine War: A developed battlespace with proxy actors, escalation ladders and enemy labels - Jakobsson, André Ken; Nielsen, Liv (Politica, 2023)
Russia’s invasion of Ukraine ushers in a new era of conflict between technologically advanced states, where conventional war in the physical domain merges with warfare in the cyber domain. The unique character of the war in Ukraine is characterized by an expanded battle space, where the military logic penetrates the civilian sphere and creates new conflictual relations across public and private spaces. Against this background, the article explores how the evolution of the Ukraine war informs three core questions of the cyber domain. The first question regards the relationship between the state and non-state actors, with an emphasis on the use of cyber proxies in the war focusing on Ukraine’s IT army. The second question regards deterrence and escalation of the conflict through the cyber domain’s escalation ladder and strategic signaling, which is expanded upon through an escalation grid. The third question concerns attribution, which is a politically charged affair where the actor behind cyber operations is labeled an adversary. The article concludes on how these preliminary experiences from the war can inform use of the cyber domain in future conflicts.